Four new species of Pleurothallis (Orchidaceae: Pleurothallidinae) from the Valle del Cauca Department in Colombia - Karremans Lok, Adam Philip (2017)
Pleurothallis indecora, P. juvenilis, P. lueriana and P. queremalensis are described from material collected in the municipality of Dagua, department of Valle del Cauca, Colombia. The four species were found during field inventories of the Orchidaceae in San José del Salado and El Queremal, they are illustrated, and a comparison with their closest relatives is provided.